MANAJEMEN PESANTREN MAHASISWA (Studi Kasus Manajemen Pesantren Aji Mahasiswa Al-Muhsin Yogyakarta) - Salim, Samsudin; Makhshun, Toha (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
Article entitled "Management of Islamic Boarding School (Case Study at Al-Muhsin Student Islamic Boarding School of Yogyakarta)" intended to see as far as the management development at Al-Muhsin Student Islamic boarding school. The main problem in this research is to know how the management development at Al-Muhsin Student Islamic boarding school. There are three data collection techniques used in this study, namely: (1) observations, to obtain data on the implementation of the management development at Al-Muhsin Student Islamic Boarding School; (2) interviews, to get clearer, more complete, and profound information about the management development at Al-Muhsin Student Islamic Boarding School; (3) documentation, to obtain historical documents of management formulation. While the data analysis used is descriptive interpretative. The results showed that; Al-Muhsin Student Islamic Boarding School of Yogyakarta has innovative steps and strategies in developing a management; management was interpreted according to the needs of the school and the community namely through activities that called the management development of Al-Muhsin Islamic Boarding School, which was applied to the learning of faith and had been carried out by the teachers very well and efficiently.Keywords: Management, Pesantren,